1001 inventions that changed the world since 2600000 BCE - Jack Challoner(Ed.) (Gurgaon Cassell Illustrated (Great Britain), 2013)
Presents a review of technological innovations and inventions, from the ancient world to the present day.
Keywords: Inventions -- History; Technological innovations